Geoconservation in the Cabeço da Ladeira Paleontological Site (Serras de Aire e Candeeiros Nature Park, Portugal): exquisite preservation of animals and their behavioral activities in a Middle Jurassic carbonate tidal flat - Machado, Susana (2021)
The Cabeço da Ladeira paleontological site in central Portugal became known as the “Jurassic Beach”. Formerly an active quarry, the site was protected in order to preserve the large exposures of a Middle Jurassic (early? Bajocian) carbonate tidal flat with an outstanding fossil record. This multidisciplinary paleontological work involving experts from several national and international research and geoconservation institutions was carried out under the umbrella of the Institute for Nature Conservation (ICNF), since this geosite is located within the Serras de Aire e Candeeiros nature park. Cabeço da Ladeira has provided exquisitely preserved body fossils, especially echinoderms, together with the exceptional preservation of their, and other, animal’s behaviors. It is also a hotspot to understand the diversity of bivalves in the Middle Jurassic. Due to the large area of the geosite, the international relevance of the findings, and the risk of weathering and destruction of the fossils, a geoconservation plan has been developed by ICNF with the support of local authorities. After several years of being open to visitors without proper control, the Cabeço da Ladeira paleontological site is now conditioned to organized groups of researchers, schools, and tourists. Some body fossils were collected for studies and included in the national collections of the Geological Museum (Lisbon). Moreover, casts have been made to protect holotypes of trace fossils, also providing ways to replicate this fossil record in temporary exhibitions. A long-term experimental study to conserve the limestone bedding plane exposures and their fossil contents was started in order to develop the best geoconservation strategy with an aim to reduce the damage produced by the increasing tourist demand on natural sites. Cabeço da Ladeira and other geosites in protected areas are key to communicating an evolutionary approach to environmental education, and their geoconservation must be a priority to improve their long-term use as (geo)tourism attractions.